Identifying Organic Carbon Sources in Surface Sediments of Mangrove Forests from Mui Ca Mau National Park Using Stable Isotope Analysis - Tai Tue, Nguyen; Viet Dung, Luu; Dinh Thai, Nguyen; Trong Nhuan, Mai (VNU Journal of Science: Earth and Environmental Sciences; Vol 34 No 4DO - 10.25073/2588-1094/vnuees.4287, 2018)
Abstract: The objective of the present research aims to identify the distribution and sources of organic carbon in surface sediments of mangrove forests from Mui Ca Mau National Park using stable isotope analysis method. Results showed that water content, organic matter content, total nitrogen, total organic carbon and C/N ratios in surface sediments of the fringe mangrove forest were lower than those of the interior forest. In contrast, the bulk sediment density, δ 13 C and δ 15 N in surface sediments of the fringe mangrove forests were higher than those of the interior forest. The non-linear relationship between δ 13 C and C/N ratios indicated that tidal particulate organic matter and phytoplankton were primary organic carbon sources in surface sediments of the fringe mangrove forest whereas the sedimentary organic carbon in the interior mangrove forest mainly originated from mangrove litters. The present study demonstrated that the distribution and sources of organic carbon in surface sediments of mangrove forests from Mui Ca Mau National Park are changed following the succession of mangrove forests and the distance from the river bank towards the interior mangrove forests. Results from the present study will contribute the scientific fundamental for implementing the studies that aim to examine the ecological functions of mangrove forests in maintaining the biodiversity of aquatic animals and to reconstruct the paleoenvironment in the mangrove intertidal zone using stable isotopes. Keywords: Mangrove forest, sediments, organic carbon, sources, stable isotopes, Mui Ca Mau. references [1] Donato, D.C., et al., Mangroves among the most carbon-rich forests in the tropics. Nature Geosci, 2011. 4(5): p. 293-297. [2] Tue, N.T., et al., Tracing carbon transfer and assimilation by invertebrates and fish across a tropical mangrove ecosystem using stable isotopes. Marine Ecology, 2017. 38(5): p. e12460-n/a. [3] Nagelkerken, I., et al., The habitat function of mangroves for terrestrial and marine fauna: A review. Aquatic Botany, 2008. 89(2): p. 155-185. [4] Hong, P.N. and H.T. San, Mangroves of Vietnam. 1993, Bangkok, Thailand: IUCN. [5] Kon, K., H. Kurokura, and K. Hayashizaki, Role of microhabitats in food webs of benthic communities in a mangrove forest. Marine Ecology Progress Series, 2007. 340: p. 55-62. [6] Connolly, R., D. Gorman, and M. Guest, Movement of carbon among estuarine habitats and its assimilation by invertebrates. Oecologia, 2005. 144(4): p. 684-691. [7] Sanders, C.J., et al., Organic matter content and particle size modifications in mangrove sediments as responses to sea level rise. Marine Environmental Research, 2012. 77(0): p. 150-155. [8] Tue, N.T., et al., The application of δ13C and C/N ratios as indicators of organic carbon sources and paleoenvironmental change of the mangrove ecosystem from Ba Lat Estuary, Red River, Vietnam. Environmental Earth Sciences, 2011. 64(5): p. 1475-1486. [9] Tinh, H.Q., et al., Composition and Structure of the Mangrove Forest at the Protected Zone of Ca Mau Cape National Park, Vietnam. Journal of Environmental Science and Management, 2009. 12(1). [10] Tue, N.T., et al., Carbon storage of a tropical mangrove forest in Mui Ca Mau National Park, Vietnam. CATENA, 2014. 121(0): p. 119-126. [11] de Graaf, G.J. and T.T. Xuan, Extensive shrimp farming, mangrove clearance and marine fisheries in the southern provinces of Vietnam. Mangroves and Salt Marshes, 1998. 2(3): p. 159-166. [12] Tue, N.T., et al., A cross-system analysis of sedimentary organic carbon in the mangrove ecosystems of Xuan Thuy National Park, Vietnam. Journal of Sea Research, 2012. 67(1): p. 69-76. [13] Mullarney, J.C., et al., A question of scale: How turbulence around aerial roots shapes the seabed morphology in mangrove forests of the Mekong Delta. Oceanography, 2017. 30(3): p. 34-47. [14] Krishna, M.S., et al., Sources, Distribution and Preservation of Organic Matter in a Tropical Estuary (Godavari, India). Estuaries and Coasts, 2014: p. 1-16. [15] Bouillon, S., et al., Sources of organic carbon in mangrove sediments: variability and possible ecological implications. Hydrobiologia, 2003. 495(1): p. 33-39. [16] Nguyen, P.T., et al., Quantifying organic carbon storage and sources in sediments of Dong Rui mangrove forests, Tien Yen district, Quang Ninh province using carbon stable isotope. Vietnam journal of earth sciences, 2016. 38(4): p. 297-306. [17] Quy, T.Đ. and N.T. Tuệ, Phân bố tổng carbon hữu cơ (TOC), tổng nitơ (TN), tỷ số TOC/TN và giá trị đồng vị bền carbon (δ13C) của vật chất hữu cơ trong trầm tích. Tạp chí Các khoa học về Trái đất, 2012. 33(4): p. 616-624. [18] Xiong, Y., et al., Soil carbon storage in mangroves is primarily controlled by soil properties: A study at Dongzhai Bay, China. Science of The Total Environment, 2018. 619-620: p. 1226-1235. [19] Yang, J., et al., Sediment deposits and organic carbon sequestration along mangrove coasts of the Leizhou Peninsula, southern China. Estuarine, Coastal and Shelf Science, 2014. 136(0): p. 3-10. [20] Marchand, C., Soil carbon stocks and burial rates along a mangrove forest chronosequence (French Guiana). Forest Ecology and Management, 2017. 384: p. 92-99. [21] Tue, N., et al., Sources and exchange of particulate organic matter in an estuarine mangrove ecosystem of Xuan Thuy National Park, Vietnam. Estuaries and Coasts, 2012. 35: p. 1060-1068. [22] Gonneea, M.E., A. Paytan, and J.A. Herrera-Silveira, Tracing organic matter sources and carbon burial in mangrove sediments over the past 160 years. Estuarine, Coastal and Shelf Science, 2004. 61(2): p. 211-227. [23] Wooller, M., et al., Carbon and nitrogen stable isotopic variation in Laguncularia racemosa (L.) (white mangrove) from Florida and Belize: implications for trophic level studies. Hydrobiologia, 2003. 499(1): p. 13-23. [24] Dehairs, F., et al., Tracing mangrove carbon in suspended matter and aquatic fauna of the Gautami–Godavari Delta, Bay of Bengal (India). Hydrobiologia, 2000. 431(2): p. 225-241. [25] Bala Krishna Prasad, M. and A.L. Ramanathan, Organic matter characterization in a tropical estuarine-mangrove ecosystem of India: Preliminary assessment by using stable isotopes and lignin phenols. Estuarine, Coastal and Shelf Science, 2009. 84(4): p. 617-624. [26] Lamb, A.L., G.P. Wilson, and M.J. Leng, A review of coastal palaeoclimate and relative sea-level reconstructions using [delta]13C and C/N ratios in organic material. Earth-Science Reviews, 2006. 75(1-4): p. 29-57. [27] Dung, L.V., et al., Carbon storage in a restored mangrove forest in Can Gio Mangrove Forest Park, Mekong Delta, Vietnam. Forest Ecology and Management, 2016. 380: p. 31-40. [28] Kauffman, J.B. and D. Donato, Protocols for the measurement, monitoring and reporting of structure, biomass and carbon stocks in mangrove forests. 2012, Bogor, Indonesia: Center for International Forestry Research (CIFOR). 40p.